2019
DOI: 10.1373/clinchem.2019.308122
|View full text |Cite
|
Sign up to set email alerts
|

Topologic Analysis of Plasma Mitochondrial DNA Reveals the Coexistence of Both Linear and Circular Molecules

Abstract: BACKGROUND Cellular mitochondrial DNA (mtDNA) is organized as circular, covalently closed and double-stranded DNA. Studies have demonstrated the presence of short mtDNA fragments in plasma. It is not known whether circular mtDNA might concurrently exist with linear mtDNA in plasma. METHODS We elucidated the topology of plasma mtDNA using restriction enzyme BfaI cleavage signatures on mtDNA fragment ends to differentiate linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
1
23
2
Order By: Relevance
“…As shown in Figure S1A, in contrast to plasma DNA of surrogate pregnant women without Bfa I treatment exhibiting a relatively smooth size distribution of mtDNA peaked at around 60 bp, plasma DNA with Bfa I digestion displayed an irregular distribution with a series of sporadic spikes up to 550 bp. The results were largely consistent with what was previously observed in plasma DNA of liver transplant patients 14 . However, we did not observe such differences in the size distribution of nuclear DNA molecules between before and after Bfa I digestion (Figure S1B).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As shown in Figure S1A, in contrast to plasma DNA of surrogate pregnant women without Bfa I treatment exhibiting a relatively smooth size distribution of mtDNA peaked at around 60 bp, plasma DNA with Bfa I digestion displayed an irregular distribution with a series of sporadic spikes up to 550 bp. The results were largely consistent with what was previously observed in plasma DNA of liver transplant patients 14 . However, we did not observe such differences in the size distribution of nuclear DNA molecules between before and after Bfa I digestion (Figure S1B).…”
Section: Resultssupporting
confidence: 92%
“…Our data revealed that the linear and circular mtDNA coexisted in the plasma DNA of surrogate pregnant subjects. The fetal‐derived mtDNA in plasma was shown to be predominantly of a linear form (88%), which is reminiscent of the preponderance of linear liver‐derived mtDNA in the plasma of liver transplant recipients 14 . In contrast, half of surrogate maternal background mtDNA (mainly of hematopoietic and liver origin) appeared to be of circular origin.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the above-mentioned studies predominantly focused on linear DNA fragments in plasma. We have recently demonstrated that there were different topologic forms (i.e., linear as well as circular) of plasma mitochondrial DNA (mtDNA) (13). Of interest, we observed that circular mtDNA molecules were predominantly of hematopoietic origin, whereas the liver-derived ones were predominantly linear.…”
mentioning
confidence: 95%